The way we eat what food means - Learning seed (Lake Zurich, Ill. : Learning Seed, 2001)
This video explores what role food plays in our lives. It discusses food as fuel convenience, medicine, and social bond. It also looks at food and moods, food alienation, and future food
Food as fuel -- Good food bad food -- Food as medicine -- Food as a stranger -- Food as a social bond
Title from title screen
DVD Format
Keywords: Food; Nutrition